Large-scale fabrication of graphene/polyamide-6 composite as a high thermal conductivity engineering composite for thermal radiators - Cao, Weiqi; Shaker, Majid; Meng, Xiaomin; Feng, Huan (Materials Letters, 2022)
In this study, graphene was mass-produced from graphite through ultrasonic-assisted exfoliation in N-methyl-2-pyrrooxone (NMP) and then mixed with polyamides Nylon (PA6) to obtain a high thermal conductivity engineering polymer (GP6). The thermal conductivity of GP6 is 30 W m−1 K−1 and the density is 1.8 g cm−1. GP6 could be used in heat dissipation systems of LED lamps and cameras with injection molding at 260 °C, thus cutting the cost by 30% and reducing the carbon emission.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Exfoliation; Graphene; Polymeric composites; Thermal properties